Organisation of Independent Work of Students of a Technical University in Field-Specific Disciplines: Instructional Commitment of a Lecturer - Redko L. A. Lyudmila Anatolevna; Sivitskaya L. A. Lyudmila Anatolievna; Francuzskaya E. O. Evgeniya Olegovna; Yanushevskaya M. N. Marina Nikolaevna (2015, 2015)
Title screen